Granulomas caused by Mycobacterium sp. in farmed Turbot Scopthalmus maximus (Linnaeus, 1758) - JERONIMO, D.; BARBOSA, A.; RAMOS, M.; MARQUES, J.; MOREIRA, M. H.; SOUSA, J. A.; CRUZ, C.; SARAIVA, A. (Mediterranean Marine Science, 2013)
Turbot, Scophthlalmus maximus, is a Pleuronectiformes fish that occurs in northeast Atlantic along the European coast and in the Mediterranean Sea and is produced in aquaculture since the last quarter of the twentieth century. During a survey conducted in a turbot fish farm nodular formations were occasionally observed in several organs, especially in the kidney and in the spleen. Microscopic observations showed that these nodules contained acid-fast bacilli. The molecular identification of the isolated bacteria conducted to the Mycobacterium genus. Although no abnormal mortalities were evident morbidity was observed. The normal development and welfare of infected fish decrease and the condition factor, the haematocrit and the haemoglobin concentration in blood decreases significantly with the increase of nodules abundance.